INSTITUTIONAL PREREQUISITES FOR THE SUCCESSFUL IMPLEMENTATION OF A TERRITORIAL COMMUNITY DEVELOPMENT STRATEGY - Parashtin, Roman (Public Management and Policy, 2026)
The article examines the conceptual foundations of sustainable development of territorial communities in Ukraine and the role of strategic planning in ensuring economic, social, and environmental balance. It emphasizes that sustainable development directly depends on the capacity and willingness of communities to implement local development initiatives, as well as on the recognition of their specificity, which is shaped by diverse needs, resources, and governance approaches. The study highlights the need for tailored solutions based on local knowledge and initiatives, as well as the alignment of interests among public authorities, civil society, business, and the academic sector. The article determines that, under decentralization, local self-government bodies are responsible for addressing key socio-economic and environmental challenges, including inadequate infrastructure, unemployment, poverty, inefficient resource use, and limited business development opportunities. These challenges require an integrated approach to local development and the improvement of strategic planning at the level of territorial communities. It analyzes the regulatory and legal framework of strategic planning. It is found that strategic planning at the local level is a mandatory component of state regional policy and must be aligned with national and regional development priorities. The article summarizes the main requirements for community development strategies, including result orientation, inclusiveness, transparency, monitoring and evaluation, as well as consideration of the social and environmental impacts of project implementation. It is shown that the effectiveness of strategies is determined not by their formal scope but by their ability to be implemented in practice and to generate real changes in territorial development. Particular attention is paid to the institutional aspects of strategic planning, including the role of working groups as inclusive platforms for interaction, the need to take into account the real needs of the population, and the involvement of various social groups in decision-making processes. It is determined that insufficient public participation leads to distorted development priorities and reduced effectiveness of strategy implementation. The article substantiates the importance of formulating goals, objectives, and indicators based on real community needs, along with their prioritization and alignment with implementation capacity and funding sources. It is emphasized that indicators should reflect actual changes rather than merely completed activities, serving as a tool for managerial decision-making and strategy adjustment. The study concludes that strategic planning, in the context of transformation processes and recovery challenges, is a key instrument for ensuring sustainable development of territorial communities and requires a shift from a formal approach to a practice-oriented, inclusive, and results-based governance model.